Early-stage oxidation behavior at high temperatures of SiSiC cellular architectures in a porous burner. Issue 14 (1st November 2016) - Rezaei, Ehsan; Haussener, Sophia; Gianella, Sandro; Ortona, Alberto
Abstract: Early stage oxidation behavior of SiSiC cellular lattices with different cell types was studied at 1400 °C in two different environments: a porous burner and an electric furnace with stagnant air. Oxidation and silicon alloy bead formation were observed and identified as the most important factors affecting the integrity of the structures. Low melting temperature silicon-based alloys formed from the material due to presence of impurities. Having lower melting point than the thermal tests temperature, the beads exuded from the microstructure leaving pores in the substrate material and leading to enhanced oxidation on the surface. Moreover, it was observed that different lattice architectures lead to different oxidation behavior on the struts as a result of the changing gas flow paths inside each ceramic architecture.